KUALITAS LAPORAN KEUANGAN LEMBAGA AMIL ZAKAT: PERAN STRUKTUR ORGANISASI, KUALITAS AUDIT, DAN SISTEM INFORMASI: FINANCIAL REPORT QUALITY OF AMIL ZAKAT INSTITUTIONS: THE ROLE OF ORGANIZATIONAL STRUCTURE, AUDIT QUALITY, AND INFORMATION SYSTEMS - Zamil, Pradita Dien Ayu Putri; Ekawati, Evi; Susanto, Is (Universitas Riau, 2025)
An ideal financial report should be prepared with high quality to provide optimal benefits for its users. This study's objective is to analyze the effect of organizational structure, audit quality, and accounting information systems on the quality of financial report in Amil Zakat Institutions (LAZ) during the 2020–2024 period using secondary data, resulting in 12 institutions with 60 observations. The findings indicate that financial reporting quality is not much impacted by organizational structure. Likewise, the quality of audits has no bearing on the quality of financial report. On the other hand, the quality of financial report is greatly impacted by the accounting information system. By integrating organizational structure, audit quality, and accounting information system variables, By supporting the empirical data on the variables influencing the calibre of financial report in Amil Zakat Institutions, this study contributes to the corpus of literature. Furthermore, the findings provide practical insights for Amil Zakat Institutions to enhance financial report quality by reinforcing organizational structures, improving audit quality, and optimizing accounting information systems to produce reports that are transparent, accurate, additionally, in compliance with the tenets of sharia responsibility.